Socioeconomic inequalities in the use of outpatient services in Brazil according to health care need: evidence from the World Health Survey - Souza-Júnior Paulo RB; Szwarcwald Célia L; Damacena Giseli N (BMC, 2010)
Abstract Background The Brazilian health system is founded on the principle of equity, meaning provision of equal care for equal needs. However, little is known about the impact of health policies in narrowing socioeconomic health inequalities. Using data from the Brazilian World Health Survey, this paper addresses socioeconomic inequalities in the use of outpatient services according to intensity of need. Methods A three-stage cluster sampling was used to select 5000 adults (18 years and over). The non-response rate was 24.7% and calibration of the natural expansion factors was necessary to obtain the demographic structure of the Brazilian population. Utilization was established by use of outpatient services in the 12 months prior to the interview. Socioeconomic inequalities were analyzed by logistic regression models using years of schooling and private health insurance as independent variables, and controlling by age and sex. Effects of the socioeconomic variables on health services utilization were further analyzed according to self-rated health (good, fair and poor), considered as an indicator of intensity of health care need. Results Among the 5000 respondents, 63.4% used an outpatient service in the year preceding the survey. The association of health services utilization and self-rated health was significant (p < 0.001). Regarding socioeconomic inequalities, the less educated used health services less frequently, despite presenting worse health conditions. Highly significant effects were found for both socioeconomic variables, years of schooling (p < 0.001) and private health insurance (p < 0.00), after controlling for age and sex. Stratifying by self-rated health, the effects of both socioeconomic variables were significant among those with good health status, but not statistically significant among those with poor self-rated health. Conclusions The analysis showed that the social gradient in outpatient services utilization decreases as the need is more intense. Among individuals with good self-rated health, possible explanations for the inequality are the lower use of preventive services and unequal supply of health services among the socially disadvantaged groups, or excessive use of health services by the wealthy. On the other hand, our results indicate an adequate performance of the Brazilian health system in narrowing socioeconomic inequalities in health in the most serious situations of need.